THE EFFECT OF STORAGE TIME AT COLD TEMPERATURES ON THE QUALITY OF PRESTO SHORT FISH (Barbonymus schwanenfeldii) - Aurelia Natasya; Widawati (Jurnal Kesehatan Tambusai, 2021)
ABSTRACTIntroductiom: The â€œtengadakâ€ presto fish (Barbonymus schwanenfeldii) is one of the perishable processed fishery products. Therefore, by storing it in a refrigerator at 5 oC the product has an optimal shelf life. The aim of this study was to determine the quality of presto fish packaged with the vacuum method with different storage periods at 5 oC in terms of organoleptic values, proximate and TBA (Thiobarbituric Acid) analysis. Method: The study design was a Completely Randomized Design (CRD) with 4 different storage periode at 5 oC namely LP0 (1 day), LP1 (10 days), LP2 (20 days), LP3 (30 days). Data were analyzed descriptively and statistical test One Way ANOVA. Results: Based on the organoleptic test, the best product preferred by the panelists was LP1 (10 Days). The Duncan's test showed that there was a significant difference between the variables of taste, aroma, and texture on the quality of â€œtengadakâ€ presto fish. The results of the proximate analysis of the best â€œtengadakâ€ presto fish every 100 g contain 55.77 g water, 10.64 g ash, 25.46 g protein, 4.99 g fat, 3.14 g carbohydrates (by deifference). The TBA analysis for at LP0 = 1.25 mg MA/Kg, LP1= 1.47 mg MA/Kg, LP2= 2.90 mg MA/Kg, LP3= 3.90 mg MA/Kg. The results of the organoleptic test showed that the selected product preferred by the panelists was LP1 (10 days) with a TBA value of 1.47 mg MA/Kg. Conclusions: Further research is needed on microorganism and chemical contamination in â€œtengadakâ€ presto fish.Â Keywords : Different Storage Time, TBA (Thiobarbituric Acid),Tengadak Fish, Presto